Ethical leadership: Early childhood center directors’ perspectives and practices in a migrant community - Tunde Szecsi; Melissa Rodriguez-Meehan; Jessica Essary; Eija Hanhimäki; Raisa Carpelan; Juan Cruz Dall’Asta; Isabel Fernandez; Elina Fonsén (Journal of Childhood, Education & Society, 2025)
This study explores dimensions of ethical leadership within the context of early childhood education (ECE) centers that serve families with migration experience in Florida, USA. The purpose is to understand what values and ethical principles are prioritized by the ECE center directors and how these principles are implemented. The datasets included interviews with six leaders at three centers about the directors’ leadership, observations of the center’s daily practices and reviews of policy documents. The data in this case study were analyzed by reflective thematic analysis. The findings indicated the directors’ commitment and values regarding quality education to eliminate poverty, and their awareness of the cultural and experiential background of children in migration. However, some misalignments surfaced between the expressed values, ethical principles and the centers’ daily operations, such as the limited presence of culturally responsive teaching. This research contributes to a deeper understanding of how ECE directors balance systemic policies with the holistic understanding of children in migration.